Continuous Photocatalysis Based on Layer‐by‐Layer Assembly of Separation‐Free TiO2/Reduced Graphene Oxide Film Catalysts with Increased Charge Transfer and Active Site. Issue 5 (22nd January 2019) - Zhang, Di; Zhang, Xu; Sun, Quan; Zheng, Shengliang; Hao, Juanyuan; Wang, You
Abstract : Although photodegradation is the most widely studied method for the purification of water, the challenges for the post‐separation of catalysts from water make the technique unsuitable for practical applications. In this study, separation‐free TiO2 /reduced graphene oxide (rGO) multilayer films were first prepared through layer‐by‐layer (LbL) assembly of TiO2 and graphene oxide (GO) on quartz slides, followed by a reduction of the assembled GO to rGO. For a proof‐of‐concept demonstration of novel continuous photocatalysis with potential for scaled‐up production, these quartz slides with TiO2 /rGO film catalysts were further assembled into slide arrays in a home‐made rectangular quartz reactor and a model pollutant Rhodamine B (RhB) solution was circularly pumped over the slide surface under UV irradiation. It was found that the as‐prepared TiO2 /rGO film catalysts show excellent enhanced photocatalytic activity for this pumping‐based continuous photocatalysis, with a photodegradation rate constant of 2.6 × 10 –2  min –1 exceeding the corresponding TiO2 /GO and TiO2 (TiO2 /PSS) samples by a factor of 11.3 and 13, respectively. The enhanced performance is attributed to the formation of Ti–O–C bonds in film catalysts bridging TiO2 and rGO to enable efficient charge separation and transfer, the Ti–O–C bond bridged electron transfer leading to increase in · O2 – active sites on the rGO surface, and the porous‐like multilayer structure. The recycling experiments showed the film catalysts are stable and could be reused with the same efficiency for at least 8 cycles. Abstract : A separation‐free photocatalytic film TiO2 /rGO with enhanced photoactivity for continuous photocatalysis was fabricated and proved to be highly suitable for scaled‐up production. The photocatalytic thin films also exhibit excellent cyclic stability, maintaining almost the same efficiency after 8 cycles, which is crucial for continuous photocatalysis.